Book review: Information technology: no longer the sole province of computers - Gackenbach, Jayne (My University, 2008)
When I was sent this book to review, my eyes lit up at the inclusion of phones in the title. I had recently been embarrassed while lecturing on cell phones by students' casual observations about their own use. I had relied on recent reviews of the literature, which stated that text messaging was not as widely used in North America as in Europe and Japan. Much to my chagrin, my students pointed out that I was wrong. As is often the case with communication studies research, the evidence lags behind the realities of use of new technologies. A year later, I understand that the cell phone is the new information technology device for immediate use and especially for the dissemination of information.
Keywords: book reviews; cell phones; Internet